Consumer Perceptions in the Selection of Non-Bank Sharia House Ownership in the City of Bandar Lampung - Andri Satria; Marselina Marselina; Heru Wahyudi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Whether the perception of religiosity, price perception, knowledge, service affects the probability of consumers in the selection of non-bank Sharia home ownership financing in Amanah Property Syariah bandar Lampung city to analyze the influence of these 4 variables on the probability of consumers choosing non-bank Sharia home ownership financing in Bandar Lampung city, a descriptive method is used with a type of quantitative research used to examine a certain population or sample.  The data will be processed with econometric analysis tools and mathematical calculations. The econometric model used to answer the research questions is factor analysis then continued with logit regression analysis. The results of the instrument validity test, each question indicator has r calculate r table so that each question indicator on the variables of religiosity, price perception, knowledge and service is valid. The H-L Statistics value is 13.5910 0.05 then the model is said to be feasible. From the t test data above, it can be seen that: For the value of prob X1 of 0.2610 where 0.05 means that the variable X1 has no effect on variable Y. For the value of prob X2 of 0.7837 where 0.05 means that variable X2 has no effect on variable Y. For the value of prob X3 of 0.0022 where 0.05 means that the variable X3 affects the variable Y. For the value of prob X4 of 0.3473 where 0.05 means that variable X4 has no effect on variable Y. Fadden R-squared is 0.183829 meaning that 18% of variable X in this study is able to affect variable Y while 84% is influenced by variable X outside this study. Based on the value of statistics z and probability, only the variables of knowledge are significant to the decision to choose non-bank Islamic home financing in Amanah Property Syariah, while the 3 variables are insignificant. All free variables (religiosity, price perception, knowledge and services) are jointly able to influence the customer's decision to choose non-bank Sharia Home Ownership Financing (PPR). However, religiosity, price perception and service factors do not have a significant effect on the decision of customers to choose non-bank Sharia Home Ownership Financing (PPR). The knowledge factor is the dominant factor in consumers' decision to choose non-bank Sharia Home Ownership Financing (PPR).